The Potential of Regional Power Sector Integration : Nile Basin Initiative Transmission and Trading Case Study - Economic Consulting Associates (World Bank, Washington, DC, 2014)
Developing countries are increasingly pursuing and benefitting from regional power system integration (RPSI) as an important strategy to help provide reliable, affordable electricity to their economies and citizens. Increased electricity cooperation and trade between countries can enhance energy security, bring economies-of-scale in investments, facilitate financing, enable greater renewable energy penetration, and allow synergistic sharing of complementary resources. This briefing note draws from the experiences of RPSI schemes around the world to present a set of findings to help address these challenges. It is based on case studies of 12 RPSI projects and how they are dealing with key aspects of RPSI, such as: (i) finding the right level of integration; (ii) optimizing investment on a regional basis; (iii) appropriate regional institutions (iv) technical and regulatory harmonization; (v) power sector reform and integration (vi) the role of donor agencies (vii) reducing emissions through RPSI; and (viii) RPSI and renewable energy.